THE EFFECT OF GLOBALIZATION ON THE DETERMINATION OF ISLAMIC LAW AS THE BASIS OF THE STATE IN INDONESIA: Analysis of the thoughts of KH. Abdul Wahid Hasyim and Ki Bagus Hadikusumo about the implementation of Islamic law in Indonesia - Suciyani Suciyani (Universitas Muhammadiyah Surakarta, 2022)
Globalization, Islamic law, Islamic figures. Nationalist figures who are considered not to represent Muslims in the formulation of Pancasila as the state ideology. The categorization of the dominance of power and thought becomes a problem among Muslims. The discourse of Islamic leaders in the formulation of Pancasila, such as ideas and concepts and their correlation with power and politics at that time. The existence of globalization is the cause and root of the problem of the classification of Islamic nationalists and secular nationalists. In the discourse theory of Michel Foucault and the paradigm theory of the characteristics of Islamic thought, the facts behind the discourses of Islamic figures are inseparable from historical factors. The writings of Islamic figures involved in the formulation of Pancasila were heavily influenced. This study only takes two Islamic figures as the focus of the study. These two great figures are the key to the determination of Pancasila, namely KH. Abdul Wahid Hasyim and Ki Bagus Hadikusumo. The involvement of Islamic leaders in the formulation of Pancasila is the impact of power. Islamic figures have a cultural role behind the scenes, because of the concept of the dichotomy of Islamic culture in Indonesia. Islam is seen as Knowledge rather than power or politics. The mention of secular nationalists and Islamic nationalists is based on ideas, not power. The discourse of Islamic figures in the formulation of the basic state is a political compromise regarding Islamic identity and Islam as values. The existence of a struggle for ideas or thoughts instead of a power struggle among Islamic leaders is mostly driven by the pressure of global political conditions. The result of the formulation of Pancasila puts forward the unity of Indonesia. The discourse of Islamic figures originated from different thoughts. The existence of the current Islamic law enforcement movement is due to the desire to power not based on Islamic scholarship.